British Military Chaplaincy in Early Victorian India - Michael Snape (Cahiers Victoriens et Edouardiens)
2007 sees the 150th anniversary of the Indian Mutiny. Although the rebellion had very important religious dimensions, very little is known about British military chaplains in the pre-Mutiny period or during the Mutiny itself. This article seeks to recover the history of this neglected subject and to highlight its significance for the wider history of British army chaplaincy and for British religious policy in post-Mutiny India.